Analisis Standard Kapasitas Pullplate pada Kayu Sengon Menggunakan Metode Uji Tarik di PT XXX - Bagus Suwiryo; Khafizh Rosyidi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Unloading is the process of removing the unit from the container, in the process it requires a tool, namely a pulplate, in the process there is often a failure of the unloading process that occurs this is due to the pulplate detaching from the wood so that the unit cannot be removed from the container under normal conditions. This study aims to analyze the strength of the screw patern in the pulplate connection with sengon wood using the tensile test method. The connection between pulplate and wood is an important aspect in wood construction, especially in structural applications. The tensile test method was used to evaluate the joint strength and performance of the patern screw under various tensile load conditions. This study was conducted by taking samples of pulplate and sengon wood connections that have been installed using a patern screw, and then subjected to a tensile force until they reach the point of failure. The analysis results will provide a better understanding of the strength of the connection between pulplate and sengon wood, as well as make it possible to optimize the screw patern design and improve the structural reliability of the connection. This research is expected to make an important contribution to the development of efficient and sustainable wood construction technology. The results showed that the new design was able to support a average load 1150.04 kg, compared to the old design which could only accommodate a average load 1115.39 kg. So we suggest changing the pullplate model currently in use and making new rules regarding pullplate installation which is expected to increase the reliability of the pullplate work function at PT XXX.